Frequency and Association of Transfusion-Transmissible Infections with Type of Blood Donors in A Regional Transfusion Center - Sabir, Nargis; Akhtar, Fahim; Ghafoor, Tahir; Lodhi, Rehan; Ali, Sadia; Fatimah, Sarah (Pakistan Armed Forces Medical Journal, 2025)
Objective: To ascertain the frequency and association of transfusion-transmissible infections (TTIs) with type of blood donors in a regional transfusion center.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Transfusion (AFIT), Rawalpindi Pakistan from Jan 2019 to Dec 2022.Methodology: A total of 275,014 donors were registered during study period. Donors were categorized according to the International Standards of Blood Transfusion, into voluntary non-remunerated blood donors (VNRD) and family-replacement donors (FRD) and into first-time donors and repeated donors respectively. All blood donors were screened for hepatitis B, hepatitis C, human immunodeficiency virus I and II and syphilis through chemiluminescent microparticle immunoassay and nucleic acid amplification test respectively. Data was analyzed using the Statistical Package for the Social Sciences version 23.00 and MS Excel 2016 software.Results: The frequency of TTIs among blood donors was 3.2%. The overall frequency of TTIs among FRD was 3.1% as compared to 0.2% in VNRD. The frequency of TTI among first- time donors was 2.9% in contrast to 0.3% in repeated donors. The most prevalent TTI was HCV (1.5%) followed by HBV (0.9%), syphilis (0.7%) and HIV (0.13%) respectively.Conclusion: TTI frequency was high in FRD and first-time donors as compared to VNRD and repeated donors respectively. HCV was the most prevalent TTI in our study. Repeated voluntary donors have least number of TTI in this study. There was statistically significant association of TTIs p- value< 0.05 with different types of blood donors.